Case for diagnosis. Pruritic erythematosquamous lesion in the auricle, - Elaine Dias Melo; Patrícia Motta de Morais; Débora Cristina de Lima Fernandes; Paula Frassinetti Bessa Rebello (Sociedade Brasileira de Dermatologia, 2020)
Abstract Chromoblastomycosis is a subcutaneous mycosis with chronic evolution that mainly affects the lower limbs and, less frequently, the auricles. Clinically, it presents with papillary verrucous, nodular, and/or tumoral lesions, whether isolated or infiltrated, forming plaques and, sometimes, atrophic in some areas. Histopathologically, it is characterized by a dermal granulomatous inflammatory infiltrate, and the diagnosis can be confirmed by the presence of fumagoid bodies in anatomopathological or direct mycological exams. The treatment to be indicated will depend on the extent and location of the lesions, using systemic antifungals, surgical removal, cryotherapy, thermotherapy, and immunoadjuvants. The present study reports an atypical presentation of chromoblastomycosis on the auricle.